2014
DOI: 10.1093/ijnp/pyu080
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Adverse Reactions During Antidepressant Treatment: A Drug Surveillance Report of German-Speaking Countries Between 1993 and 2010

Abstract: Background:Antidepressants (ADs) are known to have the potential to cause various cardiovascular adverse drug reactions (ADRs). The tricyclic antidepressants (TCAs) were first revealed to be a possible source of cardiovascular ADRs. In recent years, newer classes of ADs were also suggested to have a higher risk of cardiovascular adverse effects. In particular, the selective serotonin reuptake inhibitors (SSRIs) were suspected to have the potential to induce QTc interval prolongation, and therefore increase the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(38 citation statements)
references
References 42 publications
1
36
0
1
Order By: Relevance
“…In the intensive care unit (ICU), the prevalence of drug‐associated hypotension ranges from 23% to 81% . Hypotension causes insufficient cardiac perfusion and fatal consequences for patients in the ICU . Indeed, in a previous study, episodes of hypotension were found to exert deleterious effects, such as increased mortality rate and decreased functional outcomes, on patients with head injuries…”
Section: Introductionmentioning
confidence: 99%
“…In the intensive care unit (ICU), the prevalence of drug‐associated hypotension ranges from 23% to 81% . Hypotension causes insufficient cardiac perfusion and fatal consequences for patients in the ICU . Indeed, in a previous study, episodes of hypotension were found to exert deleterious effects, such as increased mortality rate and decreased functional outcomes, on patients with head injuries…”
Section: Introductionmentioning
confidence: 99%
“…Increased heart rate and sustained hypertension. Antidepressants with noradrenergic action, such as SNRIs (class AIIb) and bupropion (class AIIc) present the risk of increasing both blood pressure and heart rate via their sympathomimetic effects [19,24,29,69]. For this reason, the risk of hypertension is communicated within the warnings and precautions of the full prescribing information of these medications.…”
Section: Tablementioning
confidence: 99%
“…However, it should be considered that some antidepressants with noradrenergic action antagonize the α 1 -adrenergic receptor and thus counteract the increase in blood pressure, causing a very low incidence of this ADR, as is the case of mirtazapine (class AIII) and mianserin (class AIVb) [69]. In some cases, they can even cause orthostatic hypotension as usually seen with class AIVc (traditionally called tricyclic).…”
Section: Tablementioning
confidence: 99%
“…The introduction of fluoxetine highlighted the increased suicide risk during treatment initiation, which seems to be also relevant during withdrawal or dose reduction and which may be more common in adolescents or young adults. 34,35 Large case-control studies have demonstrated a higher likelihood of serious cardiovascular events in persons receiving tricyclic antidepressants (TCAs) or serotoninnorepinephrine reuptake inhibitors (SNRIs) 36 in part through corrected QT interval prolongation particularly with TCAs, a fact that may also contribute to an apparent increase in mortality. 37 SSRIs double the risk of clinically relevant gastrointestinal bleeding, especially when combined with aspirin or nonsteroidal antiinflammatory drugs.…”
Section: Time Trends In Antidepressant Usementioning
confidence: 99%